FlowChecker: A TCP Flow Analytical Framework for Network Measurements - Vinícius F. Garcia; Anderson M. da Rocha; Thales N. Tavares; Nilton C. B. da Silva; Leonardo da C. Marcuzzo (Anais do Encontro Anual de Tecnologia da Informação, 2017)
Networks are in continuous growth and with that many economic interests emerges that can eventually results in network neutrality breaking. Specialized tools aim to detect this neutrality violation by realizing measurements and analyzing network metrics such throughput and errors amount. This work presents FlowChecker, a Python framework that can execute these measurements in TCP traffic and generate results for five different networks metrics. These results can be used as a background system for network neutrality breaking tools creation.